Exposure of inhalable dust and respiratory symptoms among workers in construction industry - Wan Hafizah, Wan Mohammad Roslan (2019)
The air pollution in construction site had become great concern to the workers as it can significantly affect their respiratory health. The aim of this study was to investigate the inhalable dust exposure and its effect toward respiratory system among workers in construction industry. There were 13 workers randomly selected for indoor activities which include concrete breaking, hacking of wall and drilling. Meanwhile, another 13 workers participated as respondents for outdoor construction activities such as operation of backhoe and dump truck, housekeeping activity and construction of drain. Personal air monitoring was conducted using air sampling pump with flow rate of 1 L/min. All the workers were interviewed by using St George Respiratory Questionnaire (SGRQ). Results show that the average concentration for outdoor activities was higher (mean= 4.98mg/m3; SD= 2.72mg/m3) than indoor activities (mean= 4.19mg/m3) (SD= 2.22mg/m3). Most of inhalable dust concentration in the construction site were below the OSHA (15 mg/m3) and ACGIH (10 mg/m3) standard limits except for operation of heavy vehicles activity (backhoe =10.56 mg/m3). The prevalence of respiratory symptoms was in the range of 30.8% to 92.3% among indoor workers, while outdoor workers ranged of 23.1% to 76.9%. There was a significant correlation between personal concentration of inhalable dust and respiratory symptoms. Even though the concentration of inhalable dust below the exposure limit, however, workers still experience some of the respiratory symptoms such as coughing, phlegm secretion and shortness of breath. Therefore, the employer must provide appropriate respiratory protective equipment (RPE) with assign protection factor (APF) of 20 for the construction workers. Rescheduling and limit the working time for workers with respiratory symptoms can also be practiced in order to reduce the risk.